Internet of Things for Remote Patient Monitoring Using Cloud Computing - Zahraa Basim Mahdi; Hussien mahdi salh mahdi; Hasan Mazin Ibrahim; Hamzah Talib Salman Al-Bayati (American Journal of Botany and Bioengineering, 2025)
One way to reduce hospitalizations and improve healthcare is to move from constant monitoring in health facilities to remote patient monitoring. The internet of things (IoT) is emerging as a relevant choice for remote monitoring and sensing. In general, modern IoT systems find massive use in lives, cities, environments, industries, and health. Particularly in the health sector, IoT is also finding ample use in the monitoring and treatment of chronic diseases (like diabetes and blood pressure control) using custom fitness programs and care of elderly persons (eHealth). Moreover, the IoT-supported patient monitoring and remote telemetry using sensor-embedded watches, textiles, or vitals-measuring appliances aim to improve the healthcare system and reduce its associated costs.